Some Observations On The Catering Services In The Indian Railways - Bansal R.K; Sharma V (Wolters Kluwer Medknow Publications, 1997)
Research question: How well does the food hygiene add safety practices of the railway dining car compare with the model regulations for food safety? Objectives: To observe and analyse the catering services of the dining cars and to correlate it to the hazards that may accrue with the consumption of contaminated food. Design: Cross-sectional study. Setting: An administrative zone of the Indian Railways. Participants: Two Railways dining cars. Study Variables: Dining car infrastructure, food preparation and catering, food handlerâ€s hygiene and health. Outcome Variables: Overall quality of catering services. Results: The infrastructure of the railway dining cars, the hygienic practices observed by the food handlers and the entire catering process from storage of the raw food articles onwards till the consumption of the food by the passengers was unsatisfactory and fraught with health hazards. Almost all the model regulations for food safety had been flouted. Conclusion: There seemed to be no detailed â€˜modus operandiâ€ for the monitoring and surveillance of the catering operations of the dining cars, which were potentially conducive to the transmission of food â€" borne infections.